2004
DOI: 10.1128/aem.70.9.5557-5568.2004
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of a Rolling-Circle-Type Plasmid from Rhodococcus erythropolis and Application of the Plasmid to Multiple-Recombinant-Protein Expression

Abstract: We isolated, sequenced, and characterized the cryptic plasmid pRE8424 from Rhodococcus erythropolis DSM8424. Plasmid pRE8424 is a 5,987-bp circular plasmid; it carries six open reading frames and also contains cis-acting elements, specifically a single-stranded origin and a double-stranded origin, which are characteristic of rolling-circle-replication plasmids. Experiments with pRE8424 derivatives carrying a mutated single-stranded origin sequence showed that single-stranded DNA intermediates accumulated in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
111
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 128 publications
(114 citation statements)
references
References 42 publications
(49 reference statements)
1
111
0
1
Order By: Relevance
“…The hsaA gene was amplified using a forward primer (GCAATAGCATATG-CATCACCATCACCATCACATCGAAGGTAGGACGTCC-ATTCAACACGTGATG), which introduced an NdeI site, six codons for histidine, and a Factor Xa recognition site, and a reverse primer (GCCAAGCTTGGTAGCTGTCATTTCG-CCTAGACC), which introduced a HindIII site. The amplicon was first cloned into pET41bϩ (Novogen, Oakville, Ontario) as an NdeI/HindIII fragment, its nucleotide sequence was verified, and then subcloned in pTipQC2 (33) using the same restriction sites, yielding pTipHA. The hsaB gene was amplified using oligonucleotides (CTAGCTAGCGC-TCAGATCGATCCACGCACG and GCCAAGCTTCGTCT-GCTCGCGCCACTAG) that introduced NheI and HindIII sites flanking the gene.…”
Section: Methodsmentioning
confidence: 99%
“…The hsaA gene was amplified using a forward primer (GCAATAGCATATG-CATCACCATCACCATCACATCGAAGGTAGGACGTCC-ATTCAACACGTGATG), which introduced an NdeI site, six codons for histidine, and a Factor Xa recognition site, and a reverse primer (GCCAAGCTTGGTAGCTGTCATTTCG-CCTAGACC), which introduced a HindIII site. The amplicon was first cloned into pET41bϩ (Novogen, Oakville, Ontario) as an NdeI/HindIII fragment, its nucleotide sequence was verified, and then subcloned in pTipQC2 (33) using the same restriction sites, yielding pTipHA. The hsaB gene was amplified using oligonucleotides (CTAGCTAGCGC-TCAGATCGATCCACGCACG and GCCAAGCTTCGTCT-GCTCGCGCCACTAG) that introduced NheI and HindIII sites flanking the gene.…”
Section: Methodsmentioning
confidence: 99%
“…The pTip/Nit vectors can replicate not only in R. erythropolis but also in R. fascians and R. opacus (transformation efficiencies are 3.8×10 5 , 8.2×10 2 , and 1.6×10 4 , respectively), but not in R. rhodochrous or R. ruber 24) . In contrast, it has been reported that several plasmids are maintained in broad host ranges, and these have been used for the construction of Rhodococcus-Escherichia coli shuttle vectors.…”
Section: Expression Vectorsmentioning
confidence: 99%
“…Several types of expression vectors for Rhodococcus have been developed by using two different replication origins 23,24) . One type of these vectors propagates via a q-type mechanism, while another type propagates via a rolling circle mechanism.…”
Section: Expression Vectorsmentioning
confidence: 99%
See 1 more Smart Citation
“…During the last decade, the following efforts have been directed towards the development of genetics strategies for the manipulation of Rhodococcus members: the construction of E.coliRhodococcus shuttle vectors [272][273][274], the development of transposome systems to create random transposon libraries [271,275,276] and unmarked mutagenesis deletion systems with SacB as counter selection to generate mutants as result of two consecutive DNA single crossover events [277][278][279]. Additionally, the following approaches have been recently applied in…”
Section: The Genus Rhodococcusmentioning
confidence: 99%